1986
DOI: 10.1017/s000748530001470x
|View full text |Cite
|
Sign up to set email alerts
|

Capture-recapture studies with mosquitoes of the group of Anopheles punctulatus Dönitz (Diptera: Culicidae) from Papua New Guinea

Abstract: Five capture-recapture experiments with three species of the group of Anopheles punctulatus Donitz were undertaken in four villages in Madang Province, Papua New Guinea. Females were collected in landing catches, blood-fed, marked with fluorescent powder according to time and location of capture, and released. Recaptures took place for 4-13 nights after release. A proportion of the recaptured mosquitoes was dissected for evidence of recent oviposition and gonotrophic age determination. Two models were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 17 publications
1
56
0
Order By: Relevance
“…However, other important determinants of EIR such as emergence rate, feeding cycle length and survival per feeding cycle also depend on the availability of hosts (Charlwood, 1986;Charlwood et al, 1986;Charlwood & Graves, 1987;Burkot et al, 1989;Graves et al, 1990;Service, 1991). Some studies have indicated that increasing livestock numbers from low to moderate densities may increase malaria transmission by increasing the emergence rate of mosquitoes (Focks et al, 1988;Sota & Mogi, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other important determinants of EIR such as emergence rate, feeding cycle length and survival per feeding cycle also depend on the availability of hosts (Charlwood, 1986;Charlwood et al, 1986;Charlwood & Graves, 1987;Burkot et al, 1989;Graves et al, 1990;Service, 1991). Some studies have indicated that increasing livestock numbers from low to moderate densities may increase malaria transmission by increasing the emergence rate of mosquitoes (Focks et al, 1988;Sota & Mogi, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence rate, feeding cycle length, survival and bloodmeal host choice of malaria vectors are all influenced by the availability of exposed bloodmeal hosts to the vector (GarrettJones, 1964;Charlwood, 1986;Charlwood et al, 1986;Burkot et al, 1989;Service, 1991;Minakawa et al, 1999). Because the entomological inoculation rate (EIR) of malaria is proportional to the square of the proportion of bloodmeals taken from humans (Q h ), it is very sensitive to changes in vector host choice (Koella, 1991;Killeen et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…A capture-recapture experiment was undertaken in Area #5 in December 1991. Mosquitoes from indoor resting collections were counted, dusted with fluorescent powder 18 and released in the house closest to the breeding site. For the next eight days, 14 of Survival rate estimation.…”
Section: Methodsmentioning
confidence: 99%
“…1 Briefly, Kankiya 33 and Kaduna 34,35 are in the dry Savannah region of Nigeria; Namawala is near the flood plain of the Kilombero River in Tanzania [36][37][38] and Butelgut is in the forested foothills of Madang Province in Papua New Guinea. [39][40][41] For simplicity, our model estimates EIR for the predominant vector species at each site, which are Anopheles arabiensis at Kankiya, Anopheles gambiae sensu lato, at Kaduna and Namawala, and Anopheles punctulatus at Butelgut. 1 In order to calculate the impact of the combined effects of the intervention on the human biting rate (H bt ) it is calculated from the proposed reductions in vector emergence rate (E) and mean number of human bites per lifetime (b h ) similar to equation 12 in the original model for calculating EIR: 1…”
Section: Methodsmentioning
confidence: 99%